Bioeconomy and Global Inequalities Socio-Ecological Perspectives on Biomass Sourcing and Production - Backhouse, Maria; Lehmann, Rosa; Lorenzen, Kristina; Lühmann, Malte; Puder, Janina; Rodríguez, Fabricio; Tittor, Anne (Springer Nature, 2021)
This open access book focuses on the meanings, agendas, as well as the local and global implications of bioeconomy and bioenergy policies in and across South America, Asia and Europe. It explores how a transition away from a fossil and towards a bio-based economic order alters, reinforces and challenges socio-ecological inequalities. The volume presents a historically informed and empirically rich discussion of bioeconomy developments with a particular focus on bio-based energy. A series of conceptual discussions and case studies with a multidisciplinary background in the social sciences illuminate how the deployment of biomass sources from the agricultural and forestry sectors affect societal changes concerning knowledge production, land and labour relations, political participation and international trade. How can a global perspective on socio-ecological inequalities contribute to a complex and critical understanding of bioeconomy? Who participates in the negotiation of specific bioeconomy policies and who does not? Who determines the agenda? To what extent does the bioeconomy affect existing socio-ecological inequalities in rural areas? What are the implications of the bioeconomy for existing relations of extraction and inequalities across regions? The volume is an invitation to reflect upon these questions and more, at a time when the need for an ecological and socially just transition away from a carbon intensive economy is becoming increasingly pressing.